Identificação e seleção de bactérias produtoras de quitinases - Soares, Enio Saraiva (2016)
Currently there are different approaches to synthesize and discover new compounds, but the pursuit of these products on biodiversity is still advantageous. In bioprospecting microorganisms, which often are seeking their properties that can be exploited in biotechnology products. This is the case of chitinases, enzymes that degrade chitin. Chitinases (EC 3.2.1.29) are glycosyl hydrolases type enzymes that specifically cleave β-1,4 bonds between N-acetylglucosamines units of chitin with sizes ranging from 20 kDa to 90 kDa. The main producers of chitinase are the bodies that have chitin in their cell wall or exoskeleton, such as insects, crustaceans, fungi, algae, among others. This study aimed to select and identify producing bacteria chitinase in soil samples from different coastal regions of southern Brazil. Seventeen soil samples, collected close to fishing for shellfish waste disposal sites, were prepared and seeded in four minimum culture medium containing colloidal chitin as the sole source of carbon and energy, incubated and the colonies were isolated and purified. After yielded a total of thirteen isolates that were submitted to enzymatic index test, stressed that four isolates. The four isolated genomic DNA was extracted, amplified and purified, and sequenced region encoding 16S rRNA of these organisms. Bacteria were then pooled and identified by construction of a phylogenetic tree. The results showed the presence of the species Paenibacillus illinoisensis and Paenibacillus chitinolyticus and two members of the genus Bacillus. Future studies may indicate the possibility of its use as a source of genes for biotechnological applications such as the production of new biopesticides.